(untitled) (Revista de História Regional, 2007)
This work analyzes the history of a small colonel of a Town District in the south part of Minas Gerais Brazilian State. This article portrays a common process of relations and also of transformations during the Second half of the last century. We will make a small reconstruction of the political live of Minas Gerais that focuses the Old Republic to explain the trajectory of Antônio Gomes de Oliveira from years 40. Finally we explain how the political life had transformed at the end of the 20th century.